2022
DOI: 10.1097/jom.0000000000002538
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Depression in University Faculty, Staff, and Health Care Workers Using an Automated Mental Health Screening Tool

Abstract: Objective: This study aimed to examine relationships among worked hours, stress, sleep hours, burnout, posttraumatic stress disorder (PTSD), anxiety, and depression reported by academic medical center employees. Methods: Employees completed an anonymous electronic mental health survey with automated feedback that included self-help and professional local resources. Data were analyzed using structural equation modeling. Results: Eighty percent of participants reported (n = 693) medium/high stress, 58% reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The results of this study also showed the importance (not only from an occupational health and health promotion perspective) of creating general conditions that support health promotion with the aim of preventing the risk of mental disorders such as anxiety disorders, depression, or burnout [47,48]. Various studies have proven the connection of mental or other diseases in the absence of stress compensation [4,49,50]. Health promotion interventions are necessary to counteract career changes in the face of persistently high stress and inadequate compensation.…”
Section: Discussionmentioning
confidence: 61%
“…The results of this study also showed the importance (not only from an occupational health and health promotion perspective) of creating general conditions that support health promotion with the aim of preventing the risk of mental disorders such as anxiety disorders, depression, or burnout [47,48]. Various studies have proven the connection of mental or other diseases in the absence of stress compensation [4,49,50]. Health promotion interventions are necessary to counteract career changes in the face of persistently high stress and inadequate compensation.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have shown that anxiety and depression can both impact job burnout through other mediating variables (66,67). Additionally, other investigations have revealed that burnout can serve as a mediating factor in the regulation of anxiety and depression (68)(69)(70). In the current research, we have developed a hypothesis positing that anxiety could potentially exert an indirect influence on burnout through the mediating factor of depression.…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, we need positive, preventive, health-focused interventions to pre-emptively improve resiliency, coping, and engagement for all persons connected to academic settings. Fortunately, we do have a growing number of evidencebased resources, programs, and expert clinicians in the field (Aryankhesal et al, 2019;Melnyk et al, 2020;Sinsky et al, 2020;Tucker et al, 2022). However, our translation of these programs across the nation in both small or large, private or public, land-grant or religious-affiliated institutions is slow and uneven.…”
Section: Editorialmentioning
confidence: 99%